Design of Wet Media Digital Thermometer Calibrator Based on ATmega328p - Dyah Titisari; Syaifudin Syaifudin; Yoga Prabowo (Jurnal Teknokes, 2022)
Temperature calibration is an activity that formed the relationship between values indicated by a measuring instrument or measuring system with the value - the value relating to the temperature scale that measured under certain conditions. A clinical thermometer is a device that doctors use to measure the temperature inside a patient's body. In the field of calibration, the suitability of medical device readings with the permissible standard values ​​(tolerance values) is very necessary so that the readings are kept accurate. The purpose of this research is to make a digital wet media thermometer calibrator based on the ATmega32p to monitor the performance of the thermometer with a temperature setting of 35 °C – 40 °C in order to maintain its accuracy. The design of this calibrator consists of a wet heater circuit using a DS18B20 temperature sensor which is processed by a minimum ATmega328p system, then will be displayed on a 2x16 LCD. This tool is made to make it easier to calibrate the thermometer so that its accuracy is maintained. Thermometer calibration is done by comparing the module with a calibrated standard measuring instrument. The measurement of the instrument against the setting temperature has the smallest error of 0% and the largest of 0.25%. Meanwhile, the measurement of the instrument against a standard thermometer (which has been calibrated) has the smallest error value of 0% and the largest of -1.17%.